1988
DOI: 10.2136/sssaj1988.03615995005200030038x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Norway Spruce Growth From Soil and Topographic Properties in New York

Abstract: Soil‐site productivity relationships for Norway spruce (Picea abies (L.) Karst.) were studied on a single, but widespread soil catena (Bath‐Lordstown‐Mardin‐Volusia; ∼1.1 million ha) in central New York. Soils and vegetation data collected from 37 unthinned plantations (45‐55‐yr old) were used to develop multiple regression soilsite predictor equations and discriminant classification functions. Efforts were made through sampling procedures to reduce extraneous sources of variation inherent in many previous soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Soil samples (0-10 cm depth) were used to describe the characteristic of forest soils in accordance with the methodology proposed by Jokela et al (1988), particularly because the changes caused by environmental or to pographic factors are more prominent and relevant (e.g., on organic matter and soil bio chemical properties) on the upper layer of the soils.…”
Section: Soil Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Soil samples (0-10 cm depth) were used to describe the characteristic of forest soils in accordance with the methodology proposed by Jokela et al (1988), particularly because the changes caused by environmental or to pographic factors are more prominent and relevant (e.g., on organic matter and soil bio chemical properties) on the upper layer of the soils.…”
Section: Soil Samplesmentioning
confidence: 99%
“…appropriate stand va riables are not available. Studies based on soil-growth relationship (soil-site method) have been carried on for a wide range of spe cies elsewhere (e.g., Harding et al 1985, Jokela et al 1988, Monserud et al 1990, Pacheco 1991, Wang 1995, Bravo & Montero 2001, but very few soil-site studies have been reported for Stone pine (Bra vo-Oviedo & Montero 2005). Site index is a variable surrogate of the net stem growth that can be harvested in traditional forestry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os enfoques mais holísticos, empregando estatística multivariada e envolvendo múltiplos fatores simultaneamente (clima, solo, relevo, vegetação, geologia), levam a melhores resultados (Spurr & Barnes, 1980;Laar, 1987), razão por que têm sido usados no desenvolvimento de vários sistemas de classificação de sítios (Pregitzer & Barnes, 1984;Harding et al, 1985;Hix, 1988;Jokela et al, 1988;Burton et al, 1991;Corns, 1992;Fincher & Smith, 1994).…”
Section: Introductionunclassified